Blood dendritic cells: “canary in the coal mine” to predict chronic inflammatory disease? - Miles, Brodie; Abdel-Ghaffar, Khaled A.; Gamal, Ahmed Y.; Baban, Babak; Cutler, Christopher W. (Frontiers in Microbiology, 2014)
The majority of risk factors for chronic inflammatory diseases are unknown. This makes personalized medicine for assessment, prognosis, and choice of therapy very difficult. It is becoming increasingly clear, however, that low-grade subclinical infections may be an underlying cause of many chronic inflammatory diseases and thus may contribute to secondary outcomes (e.g. cancer). Many diseases are now categorized as inflammatory-mediated diseases that stem from a dysregulation in host immunity. There is a growing need to study the links between low-grade infections, the immune responses they elicit, and how this impacts overall health. One such link explored in detail here is the extreme sensitivity of myeloid dendritic cells (mDC) in peripheral blood to chronic low-grade infections and the role that these mDCs play in arbitrating the resulting immune responses. We find that emerging evidence supports a role for pathogen-induced mDCs in chronic inflammation leading to increased risk of secondary clinical disease. The mDCs that are elevated in the blood as a result of low-grade bacteremia often do not trigger a productive immune response, but can disseminate the pathogen throughout the host. This aberrant trafficking of mDCs can accelerate systemic inflammatory disease progression. Conversely, restoration of DC homeostasis may aid in pathogen elimination and minimize dissemination. Thus it would seem prudent when assessing chronic inflammatory disease risk to consider blood mDC numbers, and the microbial content (microbiome) and activation state of these mDCs. These may provide important clues (“the canary in the coal mine”) of high inflammatory disease risk. This will facilitate development of novel immunotherapies to eliminate such smoldering infections in atherosclerosis, cancer, rheumatoid arthritis, and pre-eclampsia.